Molecular Identification of Ladybird Beetles (Coccinella: Coccinellidae) Using DNA Barcodes - Yosur Gamal Fiteha; Mohamed Abdel-Salam Rashed; Ramadan Mohamed Ali; Aya Mohamed Abdel-Salam Hammad; Ahmed Saber Mohamed Bream; Mahmoud Magdy (Journal of Scientific Research in Science, 2022)
DNA barcoding is a molecular genetics technique commonly applied for species identification based on the cytochrome c oxidase subunit I (COI) gene located on the mitochondrial DNA genome. Based on our analysis, the DNA barcodes were generated from 16 specimen of Coccinella (family Coccinellidae). All the samples were collected from diverse sites in Egypt and Libya. Morphological traits based on the number of dorsal spots, DNA extraction, PCR amplification of COI, sequencing, nucleotide BLAST, and phylogenetics analyses were used to classify the specimens. A phylogenetic tree was constructed using the maximum likelihood method, including 46 COI sequences (the study and NCBI sequences). Three Coccinella clusters were defined and classified as Coccinella septempunctata, Coccinella novemnotata, and Coccinella undecimpunctata each species clustered into a unique branch. DNA barcodes discriminated clearly against the analyzed species. This study validated the COI efficiency as a marker for DNA barcoding of insects (Coccinella, family Coccinellidae).